A novel reverse phase high-performance liquid chromatography method for standardization of Orthosiphon stamineus leaf extracts - Saidan, Noor Hafizoh (Pharmacognosy Res, 2015)
BACKGROUND: Orthosiphon stamineus Benth. (Lamiaceae) is a traditional medicinal plant which has been used in treating various ailments such as kidney diseases, bladder inflammation, arthritis and diabetes. The leaves contain high concentration of phenolic compounds, thus, rosmarinic acid (RA), 3’-hydroxy-5, 6, 7, 4’-tetramethoxyflavone (TMF), sinensetin (SIN) and eupatorin (EUP) were chosen as a marker compounds for standardization of various O. stamineus leaf extracts. OBJECTIVE: The aim was to develop and validate a new high-performance liquid chromatography (HPLC) method for quantification of 4 marker compounds (RA, TMF, SIN, EUP) in various O. stamineus leaf extracts. MATERIALS AND METHODS: The method was developed and validated using RP-HPLC-diode-array detection at 320 nm for accuracy, precision and limits of detection and was applied for quantification of it markers in five different extracts prepared in solvents with increasing polarity, using a gradient mobile phase 0.1% formic acid: Acetonitrile at a flow rate of 1 ml/min on reverse phase acclaim polar advantage II C18 column (3 μm, 3 × 150 mm) with 18 min separation time. RESULTS: The developed method provided satisfactory precision, and the accuracy of this method was in the range of 90.2% to 105.5%. All of 4 compounds showed good linearity at R2 > 0.999. CONCLUSION: The developed method is a simple, cost effective with shorter run time (18 min) in comparison to previous methods (30 min) and utilization of environmental-friendly solvents system. Therefore, this method has the potential to replace currently used methods in the routine standardization work of O. stamineus extracts, raw materials and its commercial products.